PENGARUH AKTIVITAS, LEVERAGE DAN PERTUMBUHAN PERUSAHAAN DALAM MEMPREDIKSI FINANCIAL DISTRESS (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2013-2015) - Aprilyandhika Putri Wulansari; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2017)
This study aimed to examine the effect of activity, leverage, and firm growth to predicting financial distress in the manufacturing companies listed on the Indonesia Stock Exchange. The population are all manufacturing companies listed on the Indonesia Stock Exchange in 2013-2015. Samples was determined by purposive sampling method, sample obtained as much as 102 companies. The techniques of data analysis used is logistic regression analysis, data processing with SPSS version 16.0. The results of study concluded that activity as measured by inventory turnover has no effect in predicting financial distress leverage as measured by debt to equity ratio has a positive and significant effect in predicting financial distress and firm growth as measured by sales growth has a negative and significant effect in predicting financial distress.